Soil samples from sporotrichosis transmission belt area: Searching for fungal species and their antagonistic activity against Sporothrix brasiliensis - Lara da Costa, Gisela; Escórcio Ferreira, Isabella; Corrêa-Moreira, Danielly; Marinho, Anna; Benedito de Almeida, Adilson; Antônio Pereira, Sandro; Moraes Borba, Cintia; Marques Evangelista Oliveira, Manoel (Frontiers in Cellular and Infection Microbiology, 2022)
Since 1998, the state of Rio de Janeiro, Brazil, has become a public health problem regarding sporotrichosis, a disease caused by Sporothrix spp. involving contact with infected cats. Efforts to isolate these species from environmental sources are not always successful. In our study, soil from residences situated in cities of Rio de Janeiro where cats with sporotrichosis live was collected and cultured an attempt to isolate Sporothrix spp. but it was not successful. However, other saprophytic fungal species were isolated from soil and identified and among them Purpureocillium lilacinum was the most frequent. From there, we decided to study the in vitro interaction of this species with S. brasiliensis, the principal agent that causes sporotrichosis in this state. The results showed that ten isolates of P. lilacinum inhibited the radial mycelial growth of S. brasiliensis with different percentage of inhibition. The interaction between them revealed the pattern described as overgrowth by antagonist. In conclusion, our data suggest that fungal species with very fast growth and capable of producing metabolites could hinder the growth of Sporothrix spp., it also opens the way for the identification of secondary metabolites with biological activity that could be tested against pathogenic fungi.